2019
DOI: 10.1212/wnl.0000000000007032
|View full text |Cite
|
Sign up to set email alerts
|

Blood neurofilament light chain as a biomarker of MS disease activity and treatment response

Abstract: ObjectiveTo assess the value of blood neurofilament light chain (NfL) as a biomarker of recent, ongoing, and future disease activity and tissue damage and its utility to monitor treatment response in relapsing-remitting multiple sclerosis.MethodsWe measured NfL in blood samples from 589 patients with relapsing-remitting multiple sclerosis (from phase 3 studies of fingolimod vs placebo, FREEDOMS and interferon [IFN]-β-1a, TRANSFORMS) and 35 healthy controls and compared NfL levels with clinical and MRI-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
447
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 404 publications
(500 citation statements)
references
References 23 publications
(33 reference statements)
21
447
6
Order By: Relevance
“…A secondary, post hoc analysis employed a baseline sNfL cut‐off of 30 pg/mL . The PwMS were divided based on sNfL levels of <30 or ≥30 pg/mL and compared with previously described methods.…”
Section: Methodsmentioning
confidence: 99%
“…A secondary, post hoc analysis employed a baseline sNfL cut‐off of 30 pg/mL . The PwMS were divided based on sNfL levels of <30 or ≥30 pg/mL and compared with previously described methods.…”
Section: Methodsmentioning
confidence: 99%
“…The association of the risk of 6‐month CDW with 6‐month measures (NfL and active lesions) was assessed by a Cox model with the independent covariates included in the model as continuous variables and displayed by Kaplan–Meier survival curves with the independent covariates as binary variables (comparing those with 6‐month NfL ≤ 30 pg/mL vs. those with 6‐month NfL > 30 pg/mL, and those with 6‐month active lesions = 0 vs. those with 6‐month active lesions > 0). The NfL cut‐off level of 30 pg/mL is close to the geometric mean observed in RRMS patients . The multivariate models for assessing the simultaneous impact of NfL and active T2 lesions at 6 months were a generalized Poisson model for 24‐month relapses, an ANOVA model for 24‐month PBVC and a Cox model for 6‐month CDW. What is the contribution of NfL and active lesions as surrogate markers to the treatment effect on other disease endpoints: For a quantitative assessment of this contribution, an additional measure ‐ the proportion of treatment effect (PTE) on Month 24 relapses, PBVC, and disability worsening that could be attributed to the effects on NfL and active lesions at Month 6 was calculated according to Lin, Fleming and De Gruttola (Table S1).…”
Section: Methodsmentioning
confidence: 61%
“…In a randomized controlled study, Kuhle et al found that over 24 months, changes in NfL levels positively correlated with changes in EDSS score and enhancing lesions, but not with brain atrophy or T2 lesion volume . Blood NfL levels also did not correlate with disease duration . A clear understanding of NfL homeostasis and clearing mechanisms and how NfL levels in blood relate to the progressive changes in MS disease pathology does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…It is an essential component of the axonal cytoskeleton, and reflects the axonal integrity and the stability of neurons. Under conditions of acute axonal transection, NfL are released and can be found as a result, in the cerebrospinal fluid (CSF) and blood of patients with MS. Of note, ultra high versus low blood NfL levels have been associated with MRI related (increased number of gadolinium enhancing or T2 lesion load, whole brain atrophy) and clinical measures (number of relapses, disability worsening) of disease activity and evolution and may, therefore, have prognostic value for patients and clinicians [59].…”
Section: Mechanisms Of Late Axonal Loss (Fig 1)mentioning
confidence: 99%